TEORI KOMUNIKASI AGENDA-SETTING DALAM K-POP: PERAN MEDIA TERHADAP MOTIVASI, KEPUASAN, DAN LOYALITAS FANS DALAM MENDUKUNG GRUP IDOLA - Nestya Indih Mulyana; Qoni’ah Nur Wijayanti (JOURNAL SAINS STUDENT RESEARCH, 2024)
The agenda setting theory is a concept in communication studies that states that mass media has the ability to influence public attention by determining topics or issues that are considered important. In the context of K-Pop, media has an extraordinary capacity to influence the motivation, satisfaction, and loyalty of their fan base. The agenda setting theory affects the motivation, satisfaction, and loyalty of K-pop fans through mass media information that influences their experience. Positive media information increases fan satisfaction and loyalty, as well as motivates support for idol groups. Media shapes issues, influences attention, and plays a crucial role in marketing strategies and influencing fan loyalty to K-pop. Media creates narratives that affect the motivation, satisfaction, and loyalty of fans.